PNEUMOCOCCAL INFECTION VACCINAL PREVENTION EFFICACY IN CHILDREN USING PNEUMOCOCCAL CONJUGATED 7-VALENT VACCINE - N. L. Chernaya; O. B. Dadaeva; E. V. Shubina; S. E. Batorshina; V. M. Ganuzin; G. S. Ganuzina (Педиатрическая фармакология)
An assessment of pneumococcal infection immunization efficacy for 108 children 1-4 years of age using conjugated 7-valent vaccine has been conducted. Comparative analysis of the upper airways’ infections morbidity rate in children vaccinated and not vaccinated against pneumococcal infection is given. Prospective 1-year observation of children indicated high vaccinal prevention efficacy: multiplicity of acute respiratory diseases in children, including the period of adaptation to children’s preschool educational institutions, disease duration and number of disease cases requiring antibacterial therapy reduced considerably, the frequency of acute otitis media and the number of acute otitis media relapses in children also reduced.